(untitled) (Ibrahim Cardiac Medical Journal, 2019)
Background & objective: Renal Cell carcinoma (RCC) accounts for 2 – 3% of all malignant adult neoplasm and is associated with a mortality of 30-40%. It is not well responding to the conventional chemo and radiotherapy and in early stages of the disease,radical nephrectomy is the treatment of choice. A detailed clinoco-pathological study is of paramount importance to understand its management. The aim of this study is to describe the clinical characteristics and histopathological spectrum of RCC. Methods: This Cross-sectional descriptive study was carried out in the Department of Urology, BIRDEM General Hospital and Dhaka Medical College Hospital over a period 10 months from June 2013 to March 2014. All FNA positive renal cell carcinomas were included in the study. A total of 100 cases of RCC irrespective of age and sex were selected and their anatomical distribution, clinical presentation, stage at presentation and histopathological type were studied. Result: The peak incidence of renal cell carcinoma was observed to be between 4th and 5th decades of life. The median age was 52.3 years. A male predominance was observed in the series with male-to-female ration being 3:1. Two-thirds (67%) of the patients were diagnosed incidentally, 23% presented with pain and heamaturia and 10% with loin mass. A sizable proportion of the patients was found to have paraneoplastic syndrome [raised ESR (60%), hypertension (50%), anaemia(40%), weight loss (15%), pyrexia (2%)and hypercalcamia (2%)]. Tumours mainly involved the right kidney in its upper pole (55%). In 60% cases the size of the tumour extends between 3-7 cm. Most of the tumours were diagnosed at Robsing stage II (66%). Histopathological diagnosis showed that 70% had clear cell sub-type RCC, 20% papillary sub-type, 5% chromophobe and 5% othersub-types. Conclusion: Renal cell carcinoma generally occurs in older persons with a male preponderance, It occurs mainly in right kidney preferably in the upper pole. Patients usually present with paraneoplastic syndrome (raised ESR, hypertension, anaemia, weight loss etc.). The typical triad of pain, flank mass and microscopic hematuria is rare. Two-thirds of the RCC are diagnosed incidentally at Rosing stage-II and majority is of clear-cell sub type. Ibrahim Card Med J 2018; 8 (1&2): 17-22